The Effect of Addition of Carrot Flour (Daucus Carrota L) In Feeding to Color Brightness, Growth and Survival of Molly Fish (Poecilla sphenops) On Recirculation System - Yunisari Yunisari; Niken Ayu Pamukas Ayu Pamukas; Usman M Tang Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT          The purpose of this study was to determine the dose of carrot flour (Daucus carrota L) is best in increasing the brightness of body color Molly Fish (Phoecilia sphenops). This research was conducted from April to June 2017 in the Cultivation Technology Laboratory, Faculty of Fisheries and Marine University of Riau. The method used in this study is the method of exploitation using Completely Randomized Design (RAL) with one factor, four treatment levels, and three replications. The treatment in this study was P0 (Control, molly fish fed commercial pellets with 39% protein content.), P1 (Addition of 3% carrot flour, ie 30 grams of carrot flour and 970 grams of pellet flour with 39% protein content), P2 (Addition of 4% carrot flour which is 40 gram of carrot flour and 960 gram of pellet flour with 39% protein content.), P3 (Addition of 5% carrot flour which is 50 gram of carrot flour and 950 gram of pellet flour with 39% protein content). The results showed that the best treatment was on P3 (Addition of 5% carrot flour ie 50 gram of carrot flour and 950 gram of pellet flour with 39% protein content). The absolute weight growth is 1.37 grams, the absolute longevity is 0.52 cm, and the survival rate is 90%. Key words: Food Addation, Ornamental Fish, Growth.